Estudo de inibidores de corrosão em concreto armado, visando a melhoria na sua durabilidade - Silva, Djalma Ribeiro da (2007)
This thesis has as objective presents a methodology to evaluate the behavior of the corrosion inhibitors sodium nitrite, sodium dichromate and sodium molybdate, as well as your mixture, the corrosion process for the built-in steel in the reinforced concrete, through different techniques electrochemical, as well as the mechanical properties of that concrete non conventional. The addition of the inhibitors was studied in the concrete in the proportions from 0.5 to 3.5 % regarding the cement mass, isolated or in the mixture, with concrete mixture proportions of 1.0:1.5:2.5 (cement, fine aggregate and coarse aggregate), superplasticizers 2.0 % and 0.40 water/cement ratio. In the modified concrete resistance rehearsals they were accomplished to the compression, consistence and the absorption of water, while to analyze the built-in steel in the concrete the rehearsals of polarization curves they were made. They were also execute, rehearsals of corrosion potential and polarization resistance with intention of diagnose the beginning of the corrosion of the armors inserted in body-of-proof submitted to an accelerated exhibition in immersion cycle and drying to the air. It was concluded, that among the studied inhibitors sodium nitrite , in the proportion of 2.0 % in relation to the mass of the cement, presented the best capacity of protection of the steel through all the studied techniques and that the methodology and the monitoring techniques used in this work, they were shown appropriate to evaluate the behavior and the efficiency of the inhibitors